The Value of National Defense: Assessing Public Preferences for Defense Policy Options - Salmai Qari; Tobias Börger; Tim Lohse; Jürgen Meyerhoff (Center for Economic Studies and ifo Institute (CESifo), 2023)
Defense spending accounts for a large share of the budget in many countries, but the value of the resulting public good - national defense – has so far escaped assessment. Much of the literature has instead considered indirect benefits of defense spending in terms of greater economic growth or technological spillovers. In this paper, we assess the direct welfare effects of defense policy, namely an increase in the security of citizens, by means of a survey-based discrete choice experiment. Drawing on a representative sample of the German population, results suggest substantial willingness to pay for an increase in troop numbers, the establishment of a European army and an improved air defense system. The reintroduction of compulsory military service does not enjoy public support. Results further indicate substantial preference heterogeneity across respondents and policy options which we explore. As such, these findings demonstrate how methods of survey-based, non-market valuation can help to refine research in this area of public policy.
Keywords: C90; H41; H56; H60; 330; public good; national defense; non-market valuation; discrete choice experiment; willingness to pay